El bullying y su influencia en la deserción escolar de la Escuela de Educación Básica Jacinto Martín Aspiazu Peralta, Quevedo. 2023. - Santín Menéndez Jacqueline Maribel, Incógnito (2023)
The present investigation called "Bullying and its influence on school dropout at the Jacinto Martín Aspiazu Peralta School of Basic Education, Quevedo. 2023", had as its main objective to determine the way in which bullying influences school dropout in the Jacinto Martín Aspiazu Peralta Basic Education School, since it is currently known that according to the Quevedo - Mocache District, there is a 35% dropout rate of students (2,000), without determining the causes of these actions; For this reason, the need to find solutions to a problem that is present at a global and national level, such as bullying and its influence on school dropout. The research design was of a non-experimental nature, being this of an applied type, with a mixed approach (quantitative-qualitative), depending on the scope, this research was descriptive. For data collection, a probabilistic type sample was considered (66 surveys were applied). Among the main findings, it was determined that 52% of the students have suffered from physical aggression, 58% from some type of verbal aggression, 59% from psychological aggression and 77% on some occasions have presented problems with academic performance. cause of being bullied at school. Concluding that bullying also occurs through the use of social networks (cyberbullying) and that within educational institutions there are power relations, hierarchies and inequalities; school violence occurs. And finally, the main cause of school dropouts is due to the socio-economic situation of each family.